STUDENTS’ PERCEPTION OF SYNCHRONOUS ONLINE DISCUSSION AMIDST COVID-19 PANDEMIC - Nurfitri Alfiah S; Amirullah Amirullah; Kisman Salija (UICELL, 2021)
Synchronous online learning in the midst of a pandemic raises several points of view such as the perception of students carrying out online learning with the Zoom application. In this research, there issue that was explored; Challenges faced by students during the synchronous learning process by students of the Makassar State University postgraduate program. This study applies a descriptive qualitative method. This research was held at Makassar State University in the second semester of the 2020/2021 academic year. The participants of this study were 18 students from one class in the Research Skill Study course. The data from the research were obtained from observations and interviews. The results of this study indicate that three factors cause obstacles to challenges in online learning, namely networks and facilities, e-learning support systems, and self-regulation. The findings of this study can be a reflection for English teachers in implementing the online learning process who will use this application while teaching can quickly look for the way out from those challenges. Keywords: Perception, Synchronous learning, Online discussion, Covid-19 Pandemic.